Spatial distribution of yield accelerations and permanent displacements: A diagnostic tool for assessing seismic slope stability - Mathews, Nicolas; Leshchinsky, Ben A.; Olsen, Michael J.; Klar, Assaf (Soil dynamics and earthquake engineering (1984), 2019)
Seismically-induced permanent displacements of slopes are commonly evaluated using the Newmark sliding block approach. The conventional Newmark approach, while convenient in application, is often applied to a singular potential failure mechanism, omits consideration of the spatial distribution of potential failure mechanisms, neglects complex yet realistic failure geometry, and does not consider the temporal evolution of the critical mechanism. The proposed diagnostic tool applies the Newmark approach within a rigorous limit equilibrium framework to produce spatial distributions of yield accelerations and seismically-induced permanent displacements, or yield maps and surface-associated displacement maps, respectively. In this study, the application and utility of these diagnostic tools are demonstrated through a sensitivity analysis considering various soil strength parameters, horizontal and vertical motions, and complex slope and failure geometries. Additionally, it is shown that the proposed diagnostic tool reasonably estimates post-seismic geometry, shown by a comparison to an experimental shake table study. Using yield and displacement maps, both coseismic displacement and the range of potentially unstable geometry may be constrained. Moreover, the spatial and temporal evolution of possible seismically-induced displacements may be considered. This tool provides a rational means of applying sliding block approaches that reduces the need to assume the surface of maximum displacement a priori while retaining the simplicity that has facilitated the application of the sliding block approach versus more complex numerical models. The proposed diagnostic tools also provide a framework for future potential analyses, as it can be modified to incorporate other slope stability methods or seismic analyses. •The proposed diagnostic tools are an extension of the traditional safety map for seismic slope stability, including a map of yield accelerations and coseismic permanent displacements.•Consideration of generalized failure geometry and rotation is considered in quantification of slope permanent displacements.•Slopes subject to seismic excitation have a single surface that yields the largest coseismic displacement, however, many other potential failure mechanisms may exhibit similar permanent displacement.•Consideration of vertical accelerations results in shifts of the surface of maximum displacement during seismic excitation.•These diagnostic tools may provide important information regarding seismic slope performance when considering complex slope geometry (e.g. tiered slopes, generalized failure geometry).